1983
DOI: 10.3354/meps011205
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic bacteria in estuaries and coastal waters of northern Massachusetts: spatial and temporal distribution

Abstract: The Essex, Parker and Ipswich River estuaries are salt marsh estuaries that empty into Ipswich Bay in northern Massachusetts, USA. The Essex estuary was the subject of a year-long study of planktonic bacteria numbers and heterotrophic activity, with monthly sampling of the entire range of water within the estuary. Both numbers and activity were fractionated into 4 sizes using Nuclepore filters. The Ipswich and Parker River estuaries were sampled along with the Essex on 5 occasions for comparison purposes. In w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
1
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 23 publications
9
45
1
1
Order By: Relevance
“…The conservative bacterial distribution relaBacterial abundances along the Hudson River estuary varied from 5 to 16 X 10' cells 1-' (Table 3). This range was consistent with the low end of ranges reported in other U.S. east coast estuaries, such as the Rhode River estuary (3.0 X 108 cells 1-l; Rublee et al 1984), the Delaware River estuary (6.5 to 10 X 108 cells I-'; Coffin & Sharp 1987, Hoch & Kirchman 1993) and in Massachusetts, USA, salt marsh estuaries (7 X 10' cells 1-l; Wright & Coffin 1983). The average cell density in the Hudson River estuary (8.6 X 108 cells 1-l) was also consistent with minimum cell counts (10 X 10' cells I-'; Findlay et al 1991b) measured in the tidal freshwater Hudson River in early spring.…”
Section: Resultssupporting
confidence: 74%
“…The conservative bacterial distribution relaBacterial abundances along the Hudson River estuary varied from 5 to 16 X 10' cells 1-' (Table 3). This range was consistent with the low end of ranges reported in other U.S. east coast estuaries, such as the Rhode River estuary (3.0 X 108 cells 1-l; Rublee et al 1984), the Delaware River estuary (6.5 to 10 X 108 cells I-'; Coffin & Sharp 1987, Hoch & Kirchman 1993) and in Massachusetts, USA, salt marsh estuaries (7 X 10' cells 1-l; Wright & Coffin 1983). The average cell density in the Hudson River estuary (8.6 X 108 cells 1-l) was also consistent with minimum cell counts (10 X 10' cells I-'; Findlay et al 1991b) measured in the tidal freshwater Hudson River in early spring.…”
Section: Resultssupporting
confidence: 74%
“…The ecological or apparent (Hoch & Kirchman 1993) Q 10 determined for BP in the NRPS (2.35, 3 to 34°C) was in the middle of that range and temperature explained about half of the variation in BP rates based on the semi-log regression analysis. This was similar to the relationships found in Narragansett Bay (Staroscik & Smith 2004), Chesapeake Bay (Shiah & Ducklow 1994a), Massachusetts salt marsh estuaries (Wright & Coffin 1983) and enrichment mesocosms (Hobbie & Cole 1984). Using the alternate Arrhenius formulation, the calculated activation energy of 0.63 eV for BP was remarkably similar to the predicted 0.62 eV from Gillooly et al (2001) and the average of 0.63 eV reported by Brown et al (2004), lending more support to the MTE predictions.…”
Section: Discussionsupporting
confidence: 71%
“…Individual estuaries are unique systems based on their geomorphic, hydrologic, climatic, and watershed characteristics, and it remains a challenge to make generalizations about the patterns and controls of estuarine BP (Wright & Coffin 1983, McManus et al 2004). The Neuse River and Pamlico Sound (NRPS) estuarine system (North Carolina, USA) has witnessed several decades of basic and applied research aimed at combating water quality problems associated with excessive anthropogenic nutrient overenrichment (Paerl et al 2006a,b), but little is known about BP dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, APA did not show any correlation (p > 0.05) with nutritional parameters including TDN, DIN, DON and DIP contents of either of the waters, indicating that the activity is not nutrient limited. It may be of relevance to point out that while some studies have reported organic matter input being a n important controlling factor of heterotrophic activity (Hollibaugh & Azam 1983, Wright & Coffin 1983, it is also agreed that in coastal and estuarine areas, factors other than substrate supply may regulate the activity (Shiah & Ducklow 1994). The latter was found to be the case at the present study site.…”
Section: Discussionsupporting
confidence: 65%